A high strain, adhesive, self-healable poly(acrylic acid) hydrogel with temperature sensitivity as an epidermal sensor. Issue 3 (27th May 2020) - Zhang, Rui; Ruan, Hengzhi; Fu, Qionglong; Zhu, Xuedong; Yao, Yuan
Abstract : A fully physically linked poly(acrylic acid) (PAA) hydrogel with temperature sensitivity was fabricated. Abstract : A fully physically linked poly(acrylic acid) (PAA) hydrogel with temperature sensitivity was fabricated. The temperature-sensitive point of the hydrogel was near 25 °C when introducing the copolymer of N -isopropylacrylamide (NIPAAM) and dopamine methacrylamide (DMA). More importantly, the hydrogels exhibited excellent self-healing properties, mechanical properties and tunable adhesive strength and could be used as epidermal sensors.